PENYULUHAN TENTANG PENTINGNYA MANAJEMEN WAKTU BAGI ANAK - Nuraini, Ririn; Ali Sahana Anggian, Lutvi; Wahyu Susiani, Ika; Lailatul Qomariyah, Darul; Fajar Sadidal, Muhammad (Journal of Islamic Science Community, 2023)
Time is something that is expensive and cannot be repeated. The inability of a person to manage it will impact on his daily life. This research aims to provide counseling to children regarding the importance of time management. The research approach used is a qualitative approach to the type of case study research. Data was collected through interviews, observation, and documentation. The analysis uses triangulation techniques. This counseling had a positive impact on the discipline of children in the Nurut Tilawah Balong Al-Qur'an Education Park. They understand more about self-discipline and want to change behavior in everyday life. They are also enthusiastic about participating in activities at the institution, they are even able to make a schedule to get used to discipline.